2011
DOI: 10.1016/j.chom.2011.04.007
|View full text |Cite
|
Sign up to set email alerts
|

A Nonredundant Role for Plasmacytoid Dendritic Cells in Host Defense against the Human Fungal Pathogen Aspergillus fumigatus

Abstract: Summary: While plasmacytoid dendritic cells (pDCs), a natural type I interferon (IFN) producing cell type, are regarded as critical for innate immunity to viruses, their role in defense against fungal infections remains unknown. We examined the interactions of pDCs with hyphae of the invasive human fungal pathogen Aspergillus fumigatus. Human pDCs spread over hyphae and inhibited their growth. Antifungal activity was retained in pDC lysates, did not require direct fungal contact, and was partially reversed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
108
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(116 citation statements)
references
References 51 publications
(68 reference statements)
6
108
1
1
Order By: Relevance
“…S100A8 and S100A9, which can collectively form a heterodimer called calprotectin (Lagasse & Clerc, 1988;Odink et al, 1987;Zwadlo et al, 1988), are involved in neutrophil recruitment and are known to be produced by epithelial cells following induction by IL-22 (Aujla et al, 2008;Kolls et al, 2008;Liang et al, 2006). S100 proteins are calcium-binding cytosolic proteins that can be expressed by multiple cell types, including alveolar epithelial cells, endothelial cells, monocytes, macrophages, neutrophils and dendritic cells (DCs) (Ehrchen et al, 2009;Foell et al, 2007;Ramirez-Ortiz et al, 2011). Importantly, calprotectin may have direct antifungal and fungistatic activity against fungi, including C. neoformans (Mambula et al, 2000;McCormick et al, 2010;Urban et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…S100A8 and S100A9, which can collectively form a heterodimer called calprotectin (Lagasse & Clerc, 1988;Odink et al, 1987;Zwadlo et al, 1988), are involved in neutrophil recruitment and are known to be produced by epithelial cells following induction by IL-22 (Aujla et al, 2008;Kolls et al, 2008;Liang et al, 2006). S100 proteins are calcium-binding cytosolic proteins that can be expressed by multiple cell types, including alveolar epithelial cells, endothelial cells, monocytes, macrophages, neutrophils and dendritic cells (DCs) (Ehrchen et al, 2009;Foell et al, 2007;Ramirez-Ortiz et al, 2011). Importantly, calprotectin may have direct antifungal and fungistatic activity against fungi, including C. neoformans (Mambula et al, 2000;McCormick et al, 2010;Urban et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…This distinction has also been observed with Aspergillus fumigatus. Ramirez-Ortiz et al showed in 2011 that pDCs are capable of inhibiting A. fumigatus hyphal growth, in contrast to neutrophils and monocytes, which are able to kill A. fumigatus (21). The inhibition of A. fumigatus growth by pDCs was shown to be mediated by calprotectin, which was released as a result of pDC death, induced by a gliotoxin produced by the fungus (21).…”
Section: Discussionmentioning
confidence: 99%
“…However, there is limited information regarding a role for pDCs in mediating the host defense against fungal pathogens. During Aspergillus infections, pDCs are required for protection (21), and mice resistant to Paracoccidioides brasiliensis exhibited higher numbers of pDCs in the lungs 96 h postinfection than mice that succumbed to the infec- 4 CFU of C. neoformans strain H99␥. Prior to and during infection, mice were treated either with an isotype control antibody or with an anti-CXCR3 antibody.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations